Paradox: Regional expenditure and GRDP in Sumatra Island 2017-2022 - Nadiya Hasna Adyanka; Heru Wahyudi; Moneyzar Usman; Dedy Yuliawan (Cita konsultindo, 2024)
Economic growth is an important role of government in a region through appropriate fiscal policy. Fiscal policy is part of government spending, namely in the form of the APBN and APBD budgets. This study aims to see how the influence of Employee Expenditure, Goods and Services Expenditure, and Capital Expenditure on GRDP on the island of Sumatra. The data used in this study are secondary data, while the analysis method used is the panel data regression method from 2017-2022 in Sumatra Island Province. This study uses dependent variables and independent variables. The dependent variable used is Gross Regional Domestic Product (GRDP) and the independent variables include Employee Expenditure, Goods and Services Expenditure, and Capital Expenditure. The results showed that employee expenditure and capital expenditure had a positive and significant effect on GRDP on the island of Sumatra, while goods expenditure had a negative and significant effect on GRDP on the island of Sumatra.